THE EFFECT OF TAHAJUD PRAYER ON STRESS - Pranata, Lilik; Irfannuddin, Irfannuddin; Ali, Zulkhair; Andraini, Trinovita (Menara Medika, 2025)
Introduction: Stress is a physical and emotional reaction that occurs when a person faces pressure or environmental changes that require them to adapt. If stress is left unchecked, it can lead to many disorders. One thing that can be done is to perform tahajud prayers. The purpose of this study is to determine the benefits of tahajud prayer on stress. Method: The research design uses a literature review method by analysing articles from databases such as PubMed, Science Direct, ProQuest, and Google Scholar, focusing on articles published between 2020 and 2025, using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart approach. After selection, six articles were found to meet the inclusion criteria. Results: Tahajud prayer therapy can reduce stress levels. Discussion: Every individual experiences different levels of stress, so the process of performing tahajud prayer must be adapted to the stress level. The activity of tahajud prayer should be performed regularly without coercion and with sincerity.